'Phubbing is happening to you': examining predictors and effects of phubbing behaviour in friendships. Issue 12 (10th September 2022) - Sun, Juhyung; Samp, Jennifer A.
ABSTRACT: Phubbing is the act of snubbing someone during face-to-face interactions by using smartphones instead of paying attention to them. Although studies have examined phubbing in many different relationships, little is known about friend phubbing (Fphubbing). The present study examines which individual factors including indicators of mental health (i.e. depression and social anxiety) and personality traits (agreeableness and neuroticism) are significantly associated with Fphubbing, and how such behaviour is relevant to relational satisfaction with friends. Also, this study investigates the mediating role of Fphubbing between the proposed predictors and friendship satisfaction. Results showed that those with higher levels of depression, social anxiety, and neuroticism were significantly related to greater friend phubbing while agreeableness was negatively related to friend phubbing. In addition, greater Fphubbing led to lower levels of friendship satisfaction. Interestingly, Fphubbing mediated the relationships between each predictor of friend phubbing and friendship satisfaction. This study provides a theoretical framework to understand Fphubbing and contributes to filling a knowledge gap of phubbing in different relationship types.